On characterizations of fixed points - Zeqing Liu; Lili Zhang; Shin Min Kang (International Journal of Mathematics and Mathematical Sciences)
We give some necessary and sufficient conditions for the existence of fixed points of a family of self mappings of a metric space and we establish an equivalent condition for the existence of fixed points of a continuous compact mapping of a metric space.